Et in Arcadia ego - Berlinger, Nancy (The Hastings Center report, 2014)
Two years ago, I was on a boat in the middle of the river that runs through Brisbane, Australia, with Sarah Winch, a medical ethicist at the University of Queensland. We were talking about the intersection of our professional work and our personal experiences of caregiving. Sarah's husband, Lincoln, had died at the age of forty-eight, four months after a late-stage diagnosis of kidney cancer. My friend Julia was the same age when she died, on November 18, 2010, after living with breast cancer for seven years. Sarah asked me, “What was it like to write guidelines on end-of-life care while your best friend was dying?”